OPTIMIZING THE ROLE OF MOTHER’S COMMUNICATIONS IN ONLINE LEARNING DURING THE COVID-19 PANDEMIC - Putra, Raditya Pratama; Yulianti, Yulianti; Rachmawati, Indri (TA'DIB: JURNAL PENDIDIKAN ISLAM, 2023)
Online learning system requires parents, especially mothers, to work hard to accompany and teach their children to learn at home. The changes in learning activity have generated ways, understandings, and feelings of mothers as parents in directing and teaching their children through online learning systems during the COVID-19 pandemic. Accordingly, this study aims to determine mothers' understanding in dealing with online learning, what methods they apply to direct and teach their children in online learning and find out how they feel about managing online learning during the COVID-19 pandemic. This study uses a qualitative method with a case study approach. The results of the study show that in terms of understanding, most mothers have no difficulties in adjusting to the technology since the media used in online learning is digital media in general; the feeling of mothers in dealing with online learning is extraordinary in terms of adapting to the system and encouraging children's enthusiasm; and the way mothers direct and teach their children by applying a variety of strategies from adopting offline concept to creating a comfortable learning environment for their children.